AN ANALYSIS OF INTRALINGUAL AND DEVELOPMENTAL ERRORS IN STUDENTS' DESCRIPTIVE TEXTS(A case study of tenth grade vocational school students in Sumedang) - Fadilah, Winda Nur (2015)
This study aims at finding out the types of intralingual and developmental errors in tenth grade students' descriptive texts. A qualitative case study was employed as the research design of the study. It involved 30 tenth grade students. The students' descriptive texts were analyzed by using classifications presented by Richards (1971) in intralingual and developmental errors. The result of the study showed that the students made 71 intralingual and developmental errors consisting of 8 errors (11.2 %) in the production of verb groups, 3 errors (4.2 %) in the distribution of verb groups, 13 miscellaneous errors (18.3 %), 7 errors (9.8 %) in the use of preposition, and 40 errors (56.5 %) in the use of articles. Those intralingual and developmental errors were caused by the students' ignorance of rule restriction, false concept hypothesized and overgeneralization. Furthermore, the interference from mother tongue also affected the occurrence of those errors. Errors in the use of articles exceeded the other types of errors with pattern omission of a as the highest errors made by the students. The omission of a is an example of the students' ignorance of L2 rule restrictions. Furthermore, it is also affected by their L1 structure sentence. Given to the results above, it is recommended that the teacher give the students remedial and detail explanation in the use of articles. Moreover, the teacher can give them exercises in order that they can determine the appropriate articles that should be used, and ask them to learn and practice to make sentences by using the articles. This activity can help the students to improve their accuracy in writing. Keywords: intralingual and developmental errors, writing, descriptive text Penelitian ini bertujuan untuk menemukan tipe-tipe error intralingual dan developmental pada deskriptif teks siswa kelas X. Pendekatan kualitatif digunakan sebagai rancangan penelitian. Penelitian ini melibatkan 30 siswa kelas X. Deskriptif teks siswa dianalisis dengan menggunakan klasifikasi yang dipersembahkan oleh Richards (1971) dalam error intralingual dan developmental. Hasil dari penelitian menunjukkan bahwa siswa membuat 71 error intralingual dan developmental terdiri dari 8 error (11.2%) dalam produksi kelompok kata kerja, 3 error (4.2%) dalam distribusi kelompok kata kerja, 13 bermacam-macam error (18.3%), 7 error (9.8%) dalam penggunaan preposisi dan 40 error (56.5%) dalam penggunaan artikel. Tiper-tipe error intralingual dan developmental tersebut disebabkan oleh ketidaktahuan akan aturan, hipoteses konsep yang salah dan penyamarataan yang berlebihan. Selanjutnya, campur tangan dari bahasa ibu juga mempengaruhi peristiwa error-error tersebut. Error dalam penggunaan artikel melebihi tipe error lain dengan bentuk penghilangan artikel a sebagai error tertinggi yang dibuat oleh siswa. Penghilangan artikel a adalah sebuah contoh dari ketidaktahuan siswa akan aturan yang berlaku. Selain itu, error tersebut dipengaruhi oleh struktur kalimat L1/bahasa pertama. Berdasarkan hasil penelitian di atas, telah disarankan bahwa guru harus memberi siswa remedial dan penjelasan yang detail dalam pengunaan artikel. Selebihnya, guru dapat memberi mereka latihan-latihan dengan tujuan agar mereka dapat menentukan artikel yang tepat yang harus digunakan dan meminta mereka untuk belajar dan praktek untuk membuat kalimat-kalimat dengan menggunakan artikel tersebut. Kegiatan ini dapat membantu siswa untuk meningkatkan keakuratan menulis mereka. Kata kunci: error intralingual dan developmental, menulis, deskriptif teks